Groundwater economics : selected papers from a United Nations symposium held in Barcelona, Spain - Custodio, Emilio; Gurgui, A. (Antonio), 1953- (Developments in water science, 1989)
This book contains a selection of papers presented at the Symposium and Workshop on Groundwater Economics, held in Barcelona, Spain, 19-23 October 1987. The editors' aim was to produce a publication with useful contributions, containing basic concepts, general formulations, relevant specific studies usable as reference cases, and issues of interest for developing areas and countries.